On the correlation between semantics and syntax - HOCINE, Nacira (Journal of Human Sciences, 2000)
The purpose of this study is to investigate the correlation between semantics and syntax by looking at complement – taking verbs and complement sentences in three different languages: French, English and Modern standard Arabic (MSA).                Our aim is to describe the semantic classes of complement-taking verbs and the syntactic structures of complement sentences in order to delimit some idiosyncratic features in each language under discussion, and show to what extent the three languages are comparable. Moreover, the semantic classification of complement-taking verbs where some semantic properties of verbs in English, French and MSA are analysed, showed some rough similarities and differences in the behaviour of complement – taking verbs in the three languages.Furthermore, we have tired to show through semantic classifications and sub-classification of verbs that the claim syntactic structures of complements are determined by semantic properties of main verb "is not axiomatic" because of the "loose" correlation between semantics and syntax. As there is no one-to-one correspondence between the syntactic structures of complements and semantic features of verbs, it is sometimes difficult to ascribe semantic regularities for verbs and syntactic patterns for complement sentences, especially at a cross-linguistic level